Korelasi antara Plant Awareness Disparity dan Kemampuan Identifikasi Tumbuhan pada Mahasiswa - Putra, Rinaldi Rizal; Diana Hernawati; Fitriani, Rita (INSTITUT AGAMA ISLAM NEGERI AMBON, 2025)
Plant awareness disparity (PAD) is a phenomenon that indicates individuals' lack of attention or awareness towards plants in their surrounding environment. This gap can affect the ability of pre-service biology teachers to identify plant types. This study aims to analyze the correlation between PAD and plant identification skills in preservice teachers. This study aims to analyze the correlation between PAD and plant identification skills in students. The method used is correlational with instruments in the form of PAD questionnaires and local plant identification tests. The research population was all prospective biology teachers at Siliwangi University, totaling 518 people. Samples were taken using purposive sampling techniques, including 200 preservice biology teachers in grades 1 and 2. Data analysis using a simple regression correlation test, and based on the results of the analysis, it was found that PAD has a significant influence on plant identification ability, with a coefficient of determination (R²) value of 0.75. This shows that 75% of the variation in plant identification ability can be explained by PAD, while 25% is influenced by other factors outside the measured variables. This finding indicates that increasing awareness of plant diversity can improve the skills of prospective biology teachers in identifying plants. The implications of this study indicate the importance of learning strategies to increase awareness of the existence of plants in biology education and improve the plant identification skills of prospective teachers and enrich the botanical literacy of the next generation. Keywords: Plant Awareness Disparity, Plant Identification, Preservice Teacher